Determinants of Implementation of Dental Health Promotion in Elementary School Children: Study on Teachers and Parents - Mufizarni; Cut Soraya; Mudatsir; Poppy Andriany (Al-Hijrah Indonesia, 2024)
Dental and oral health has an important role and impact on general health conditions and child development. One of the efforts to prevent dental disease early in children can be done through promotion and education about children 's dental health to parents and teachers as the closest people to the child. The purpose of this study is to determine the determinants of the implementation of dental health promotion by teachers and parents in elementary school children in Aceh Besar District. The research design method is observational analytic with a cross-sectional study approach. The subjects in this study were 110 teachers and 110 parents of elementary school children that carried out by purposive sampling. Data collection was carried out directly from respondents using a validated questionnaire. The statistical tests used were the chi square test and the logistic regression test. The results of this study indicate that the factors of knowledge, attitude, action, availability of facilities and infrastructure, motivation and participation of teachers and parents have a significant influence on the implementation of dental health promotion in elementary school children. In the subject of teachers, the most dominant variables influencing the implementation of dental health promotion in children are the availability of facilities and infrastructure (p = 0.004, Exp (B) = 5.704) and motivation (p = 0.030, Exp (B) = 2.914). In the subject of parents, the most dominant variables are participation (p = 0.000, Exp (B) = 12.803) and motivation (p = 0.001, Exp (B) = 8.899). Based on the results of the study, it can be concluded that the availability of facilities, participation, motivation and knowledge from parents and teachers are key factors in the success of implementing dental health promotion in elementary school children. Holistic interventions and approaches are needed, so as to provide a positive impact on the implementation of dental health promotion in elementary school children.